2017
DOI: 10.12659/msm.903636
|View full text |Cite
|
Sign up to set email alerts
|

Differences in ABCA1 R219K Polymorphisms and Serum Indexes in Alzheimer and Parkinson Diseases in Northern China

Abstract: BackgroundABCA1 R219K single-nucleotide polymorphisms (SNPs) was related to Alzheimer disease (AD) but not Parkinson disease (PD). Here, we analyzed the associations among ABCA1 R219K distribution, serum biomarkers, AD, and PD in a population in northern China.Material/MethodsWe used the Mini-Mental State Examination (MMSE) and the Hoehn and Yahr scale (H-Y) to evaluate AD and PD progression, separately. ABCA1 R219K was analyzed by matrix-assisted laser desorption ionization time of flight time mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…TAG levels are decreased in serum and plasma of (male) PD patients [222,223,229,230,231,232,233], even before diagnosis [234], and higher serum TAG is associated with reduced risk of idiopathic PD [235]. However, other studies have found no differences in blood TAG levels of PD patients and controls [236,237]. In the primary visual cortex of PD patients, the levels of TAG are decreased [225].…”
Section: Glycerolipidsmentioning
confidence: 99%
See 2 more Smart Citations
“…TAG levels are decreased in serum and plasma of (male) PD patients [222,223,229,230,231,232,233], even before diagnosis [234], and higher serum TAG is associated with reduced risk of idiopathic PD [235]. However, other studies have found no differences in blood TAG levels of PD patients and controls [236,237]. In the primary visual cortex of PD patients, the levels of TAG are decreased [225].…”
Section: Glycerolipidsmentioning
confidence: 99%
“…The main biological role of HDL is in cargo transport, in particular of lipids and proteins, but it is now also known to bring miRNAs to recipient cells [535]. Lower plasma HDL and ApoA1 levels have been associated with earlier PD onset [536] and higher PD risk [237,537,538,539], and HDL levels are positively correlated with disease duration [540]. Plasma levels of HDL-cholesterol are lower [229,385,541] or not different [230,233,446,447,457] in PD patients compared to controls.…”
Section: Lipoproteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The density and size of these particles are similar to those of plasma HDL [ 148 ]. ABCA1 contributes to cholesterol homeostasis and participates in the pathophysiology of neurological diseases involving the accumulation of proteins in brain cells, such as traumatic brain injury, stroke sequelae, Parkinson’s disease, and Alzheimer’s disease (AD) [ 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 ].…”
Section: Abca1 In Neurological Diseasementioning
confidence: 99%
“…The meta-analysis showed no signi cant difference in the TC level between the RR genotype population and the K allele carriers in the random model, and signi cant heterogeneity was found among all studies. After four outliers (Abellán [93] data1, Ya [105] data1, 2 and 3) detected by the meta and metafor packages were removed (Fig. S7-1 and 2), a consistent result was obtained (SMD = 0.01 mmol/L, 95%CI:-0.06 ~ 0.08, z = 0.20, P = 0.846; I 2 = 88.37%, Q = 782.18, df = 91, P < 0.001.…”
Section: Meta-analysis For Genetic Variant R219k and Tcmentioning
confidence: 99%